A signal transducers and activators of transcription (STAT) gene from Scylla paramamosain is involved in resistance against mud crab reovirus. Issue 94 (November 2019) - Deng, Hengwei; Zhang, Wenfeng; Li, Jingjing; Li, Jinling; Hu, Lei; Yan, Wenyan; Liu, Shanshan; He, Jianguo; Weng, Shaoping
Abstract: A STAT gene from Scylla paramamosain, named SpSTAT, was cloned and characterized. The full length of SpSTAT mRNA contains a 5′untranslated region (UTR) of 238 bp, an open reading frame (ORF) of 2388 bp and a 3′ UTR of 326 bp. The Sp STAT protein contains four characteristic STAT domains and showed 84% identity (90% similarity) and 44% identity (64% similarity) to Litopenaeus vannamei STAT protein and Human STAT5a/b protein, respectively. The mRNA of SpSTAT was high expressed in the intestine and eyestalk and low expressed in the heart and muscle. Moreover, expression of SpSTAT was significantly responsive to challenge of mud crab reovirus (MCRV), Poly(I:C), LPS and Staphylococcus aureus . Sp STAT could be activated by Poly(I:C) and LPS to translocate to the nucleus of Drosophila Schneider 2 (S2) cells. Sp STAT could be phosphorylated by interaction with JAK of S. paramamosain ( Sp JAK) and activated to translocate to the nucleus of S2 cells. Furthermore, Silencing of SpSTAT in vivo resulted in higher mortality rate of MCRV infected mud crab and increased the viral load in tissues, suggesting that SpSTAT could play an important role in defense against MCRV in mud crab. Highlights: The full length of Scylla paramamosain STAT ( SpSTAT ) was cloned and characterized. SpSTAT was significantly upregulated by mud crab reovirus(MCRV), Poly(I:C) and LPS. Sp STAT could be phosphorylated by interaction with Sp JAK in S2 cells. The nuclear shift of Sp STAT was observed by challenge of Poly(I:C), LPS and Sp JAK. SpSTAT could play an important role in defense against MCRV in mud crab.